Strategi Koping Ibu Penderita Diabetes yang Hamil dan Melahirkan Bayi Besar (Makrosomia) - Hadi Sukirno, Rita Setyani (Fakultas Ilmu Kesehatan Universitas Dharmas Indonesia, 2024)
Mothers with diabetes have a risk of giving birth to macrosomic babies and they are vulnerable to experiencing pressure or stress. In stressful conditions, a person needs a way to deal with the stress they face, which is known as a stress coping strategy. This study aims to describe the coping strategies used by mothers with diabetes from pregnancy to giving birth to macrosomic babies. This research method is a case study of an informant (Mrs. L) who gave birth to a baby with a birth weight of 4.8 kg and was treated in the NICU because of experiencing seizures. The data collection method for this research is semi-structured interviews. The main question of this research is how to describe the stress coping strategies of mothers with diabetes who are pregnant and give birth to macrosomic babies. The results of this research can illustrate the stress coping strategies of mothers with diabetes in facing various challenges ranging from accepting their pregnancy to accompanying macrosomic babies who need medical care. The emotional-focused coping and religious coping strategies used by the informants are more to manage emotions as a form of surrender and hope for God’s help. However, the informant also used problem-focused coping strategies while monitoring the health of herself and the unborn baby by routinely checking her pregnancy. Another form of problem-focused coping is that when the baby was being treated in the NICU, the informant tried to ensure that the macrosomia baby got the right medical care.